DESKRIPSI PEMAHAMAN KONSEP DAN KEMAMPUAN BERPIKIR KRITIS TERKAIT DENGAN PENGINTEGRASIAN AKTIVITAS PRAKTIKUM DAN TEORI DI KELAS XI SMA - Putri Triska Widya (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2018)
Chemistry had been regarded as a difficult subject for students by some reason, such as because of the abstract nature of many chemical concepts. Teachers should help students to resolve difficulties in understanding of chemical concepts. Develop students critical thinking and scientific thinking is one of several ways to help students more easily in understanding of chemical concepts. Practicum in the lab can train students to think critically and at the same time build students' understanding of the chemical concepts.The purpose of this research was to describes critical thinking skills , conceptual understanding, and correlation of critical thinking skills with students' conceptual understanding. This type of research is descriptive research. Informants in this research is the student of the second grade in SMAN 15 Padang. The instrument used in this research is essay test, CCTT-X test  and observation sheet. The results showed that class with a practicum in early learning will further develop critical thinking skills and students ' understanding of concepts rather than classes with practicum at the end of learning, and also correlation of students critical thinking with their conceptual understanding is very week.